Rapport Synthétique projet - Philipps, Joschka (Fluid Ontologies of Contestation. Social media, anti-government protest and transnational decolonization movements in Burkina Faso, 2023)
The summary of the project document sets out the main lines of the project. While contextualizing the field of research, the document presents the advantages of conducting research that reconciles interdisciplinarity between data sciences and social sciences, as well as the resources available for conducting the project and the concepts involved.
Keywords: Social media; Decolonisation; Right to Resist; Morality